The place of intravenous immunoglobulin in rheumatic diseases - N. V. Seredavkina; T. M. Reshetnyak; E. L. Nasonov (Современная ревматология)
Therapy with intravenous human immunoglobulin (IVIG) was and continues to remain essential for a number of diseases. At the same time the evidence base for IVIG use is extremely small in rheumatology. Clinical experience shows that IVIG is effective in treating thrombocytopenic purpura, Guillain–Barre syndrome, and chronic inflammatory demyelinating polyneuropathy, which develop in the presence of rheumatic diseases, such as systemic lupus erythematosus, inflammatory myopathies, and antineutrophil cytoplasmic antibody-associated vasculitides. The review considers indications for the use of IVIG, its dosage regimen, benefits, and adverse reactions and analyzes the Russian and foreign literature on this issue.